2014
DOI: 10.1093/schbul/sbt235
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Neurocognition and Negative Symptoms to Social and Role Functioning Over Time in Individuals at Clinical High Risk in the First Phase of the North American Prodrome Longitudinal Study

Abstract: The modest overlap among neurocognition, negative symptoms, and social and role functioning indicates that these domains make substantially separate contributions to CHR individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
144
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(169 citation statements)
references
References 47 publications
21
144
4
Order By: Relevance
“…A recent investigation (the North American Prodrome Longitudinal Study) on clinically high-risk (CHR) patients for psychosis reported that negative symptoms mediated the relationship between composite neurocognition and social and role functioning; such findings replicate what a previous meta-analysis of schizophrenia studies had reported [118,119]. Nonetheless, the modest overlap among neurocognition, negative symptoms, and social functioning suggests that these domains make substantially separate contributions to the outcome in CHR patients [118].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…A recent investigation (the North American Prodrome Longitudinal Study) on clinically high-risk (CHR) patients for psychosis reported that negative symptoms mediated the relationship between composite neurocognition and social and role functioning; such findings replicate what a previous meta-analysis of schizophrenia studies had reported [118,119]. Nonetheless, the modest overlap among neurocognition, negative symptoms, and social functioning suggests that these domains make substantially separate contributions to the outcome in CHR patients [118].…”
Section: Discussionmentioning
confidence: 55%
“…Nonetheless, the modest overlap among neurocognition, negative symptoms, and social functioning suggests that these domains make substantially separate contributions to the outcome in CHR patients [118]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 In other studies of CHRs, diminished verbal memory performance is related to concurrent social functioning, and also predicts later role functioning and transition to full psychosis. 2,31 Therefore, a treatment that directly improves this domain and/or that may pre-empt decline in verbal memory systems is of particular long-term clinical importance for CHR individuals.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…To date, high-risk research has predominantly focused on cognitive deficits and associated psychosocial impairments. Cognitive deficits across multiple domains are consistently observed in high-risk populations [8], are associated with structural and functional abnormalities in frontal and temporal regions [9], and predict symptom severity, social functioning, and transition to psychosis [8,[10][11][12]. These cognitive deficits are considered to reflect a domain-general impairment in cognitive control-the inhibitory and facilitatory functions necessary to maintain taskrelevant processing and goal-oriented behavior-which may represent a risk marker for future clinical and psychosocial deterioration.…”
Section: Introductionmentioning
confidence: 99%